Investigation of the Cultural Intelligence Levels of the Turkish University Students at Foreign Language Departments - Åženel, MÃ¼fit (International Journal of Language Education, 2020)
The aim of this study was to investigate and explore the level of Cultural Intelligence of students majoring at the English, German and French Departments at Samsun 19 MayÄ±s University, Faculty of Education on 2018-2019 academic year. 200 students participated in the study. Study also aimed to determine whether their Cultural Intelligence was associated with their gender, age, and departments they attended. As data collection instruments, Cultural Intelligence Scale which was developed by Ang et al. in 2007 and Demographic Information Form which was developed by the researcher were used. Cultural Intelligence Scale was adapted to Turkish and assessed by Ä°lhan and Ã‡etin in 2014. Collected data were analyzed and evaluated by SPSS 23 statistical package program. According to the results obtained from the research, it could be stated that there was a significant difference for some subcategories of Cultural Intelligence. In addition, it was observed that the students who participated in the study differed significantly in terms of the type of departments in which they studied and the high schools that they had graduated from. Regard with mean scores of the participants it was observed that mean scores of males were higher than females in terms of some variables. In the end of the paper, limitations and pedagogical dimensions of the study were discussed. Additionally, suggestions were given for future research in the light of the yielded results.